Experimental study on the mechanical behavior of BFRP-bamboo composite beam. (31st July 2019) - Lv, Qingfang; Liu, Ye
This article proposes a basalt fiber-reinforced plastic–bamboo (BFRP-bamboo) composite beam consisting of BFRP sheet and laminated bamboo, aiming at fully utilizing advantages of bamboo and BFRP to improve the mechanical behavior of the laminated bamboo beam. A two-step test program is involved: (1) double shear test for bonding behavior between the BFRP and laminated bamboo and (2) loading test for mechanical behaviors of both laminated bamboo and BFRP-bamboo composite beams. Parameters affecting the bonding behavior are firstly concluded as the coated surface resin, types of bonding materials, and interfacial treatment. Then, the failure patterns of both laminated bamboo and BFRP-bamboo composite beam are discussed based on experimental observations. Key mechanical indexes, including the yield force, yield displacement, ultimate load, ultimate displacement, ductility, and stiffness, are analyzed based on load–displacement curves of tested specimens. Besides, theoretical analyses of bearing capacity of the BFRP-bamboo composite beam, featured as fracture failure, are conducted.